Picture-Driven Technique to Enhance English Vocabulary in Grade VIII at SMP Negeri 1 Bolaang - Bandu, Magtira; Rorintulus, Olga; Ali, Muhammad Ilham (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2025)
This study aims to determine the effectiveness of the Picture-Driven technique in improving English vocabulary mastery among second grade students of SMP Negeri 1 Bolaang. This research was conducted using quantitative method. This study used a pre- experimental design with a single group for both the pre- and post-tests. The data were analyzed using statistical tests to examine variations in the pre-test and post-test scores the pupils in the second grade of SMP Negeri 1 Bolaang consisting of 25 students were the subjects of this study. There were 20 numbers for each test given the students. The results of this study show If the pre-test's average score is (35.52) The post-test is (62.56) The post-test result is higher than the pre-test. Based on this result, Pictures have an extremely important impact on pupils' vocabulary. The result of a notable rise in scores from the pre-test to the post-test indicate that images not only help in understanding the meaning of words, but also make it easier for students to pronounce them more accurately and confidently. With the stimulus in the form of image-based techniques, students can master the meaning and pronunciation of a word more effectively, so that their ability to spread knowledge increases significantly.